Impact of Institutional Reforms on Export Diversification in Selected Developing Countries - Mohammad Fardin Harighi; saeed Daei-Karimzadeh; Hosein Sharifi Renani (مدلسازی اقتصادسنجی, 2022)
Positive role of institutional reforms on economic growth and productivity has been proven. Researchers are now focusing on the factors such as R&D, export diversification and innovation influencing this relationship. In this regard, this study examines the relationship between institutional reforms and Doing Business on export diversification. For this purpose, The dynamic panel data (DPD) analysis, for sample of 54 developing countries including Iran has been used by generalized method of moments (GMM) and Arellano –Bover/ Blundell – Bond two step during the period 2005-2018. The findings indicate that institutional reforms have significant positive on export diversification in developing countries. In addition, Surgan and first and second degree auto-correlation tests explicitly supports the econometric model.